PHILOSOPHY OF SCIENCE IN THE ERA OF BIG DATA AND ARTIFICIAL INTELLIGENCE: CHALLENGES AND OPPORTUNITIES - Uqba, M Sholih Salimul; Istiadah (Al-Iqro', 2024)
This research aims to examine the challenges and opportunities faced by philosophy of science in the era of Big Data and Artificial Intelligence (AI). This era is characterized by rapid developments in the collection, storage and analysis of large and complex data, as well as advances in artificial intelligence technology that allows machines to learn and make decisions automatically. This research uses a qualitative approach with a literature study method. The main challenge faced by the philosophy of science is to overcome the complexity and infinite dimensions of the data generated. Big Data provides the ability to analyze patterns and trends that were previously difficult to detect, but on the other hand it also presents challenges in understanding the position of philosophy towards this infinite quantity and diversity of data. Philosophy of science needs to consider concepts such as truth, reliability and validity in the context of probabilistic and uncertain data. In addition, artificial intelligence also raises profound philosophical questions. Philosophy of science needs to address questions of ethics and responsibility in the use of artificial intelligence. However, the era of Big Data and AI also provides opportunities for philosophy of science. Philosophy of science can develop new methodologies to understand complex phenomena in various disciplines. It can leverage artificial intelligence to efficiently analyze data and gain deep insights. In addition, philosophy of science can play an important role in developing ethical frameworks for the use of Big Data and AI. In conclusion, the era of Big Data and Artificial Intelligence poses significant challenges and opportunities for philosophy of science in developing deep understanding and producing necessary ethical guidance